WOMEN, WAR, AND RESILIENCE IN KHALED HOSSEINI’S A THOUSAND SPLENDID SUNS - Shodiyeva Ruxshona (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: In this article, Khaled Hosseini’s A Thousand Splendid Suns explores the struggles of Afghan women living under war, patriarchy, and political instability. Through the lives of Mariam and Laila, the novel presents themes of suffering, resilience, motherhood, sacrifice, and hope. Hosseini portrays how social oppression and gender inequality shape women’s lives while also emphasizing the strength of human connection and emotional endurance. This article examines the representation of women’s experiences, the impact of war on personal identity, and the symbolic role of love and sacrifice throughout the novel.